Polymorphisms in genes hydroxysteroid-dehydrogenase-17b type 2 and type 4 and endometrial cancer risk - Karageorgi, Stalo (2010)
OBJECTIVE: Hydroxysteroid-dehydrogenase-17b (HSD17b) genes control the last step in estrogen biosynthesis. The isoenzymes HSD17b2 and HSD17b4 in the uterus preferentially catalyze the conversion of estradiol, the most potent and active form of estrogen, to estrone, the inactive form of estrogen. Endometrial adenocarcinoma is linked to excessive exposure to estrogens. We hypothesized that single nucleotide polymorphisms (SNPs) in genes HSD17b2 and HSD17b4 may alter the enzyme activity, estradiol levels and risk of disease. METHODS: Pairwise tag SNPs were selected from the HapMap Caucasian database to capture all known common (minor allele frequency>0.05) genetic variation with a correlation of at least 0.80. Forty-eight SNPs were genotyped in the case-control studies nested within the Nurses’ Health Study (NHS) (cases=544, controls=1296) and the Women’s Health Study (WHS) (cases=130, controls=389). The associations with endometrial cancer were examined using conditional logistic regression to estimate odds ratio and 95% confidence intervals adjusted for known risk factors. Results from the two studies were pooled using fixed effects models. We additionally investigated whether SNPs are predictive of plasma estradiol and estrone levels in the NHS using linear regression. RESULTS: Four intronic SNPs were significantly associated with endometrial cancer risk (p-value <0.05). After adjustment for multiple testing, we did not observe any significant associations between SNPs and endometrial cancer risk or plasma hormone levels. CONCLUSIONS: This is the first study to comprehensively evaluate variation in HSD17b2 and HSD17b4 in relation to endometrial cancer risk. Our findings suggest that variation in HSD17b2 and HSD17b4 does not substantially influence the risk of endometrial cancer in Caucasians.